Analisis Kualitas Layanan Website Pengadilan Negeri Jambi Dengan Metode Webqual 4.0 - Donzon, Allbet; Istoningtyas, Marrylinteri (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2024)
The Jambi District Court is a first-level judicial institution within the judicial system of Indonesia. The Jambi District Court's website provides various information, but it is possible that there are still issues or shortcomings, such as the website's less appealing design, the complaint service being difficult to understand, incomplete or insufficient information provided to users, the lack of responsiveness regarding complaints through external platforms (social media), and the limited information and discrepancies in the scheduled court hearings. Based on this background, this study aims to analyze user satisfaction levels with the Jambi District Court’s website using the WebQual 4.0 method. The study employs four variables: Usability Quality, Information Quality, Service Interaction Quality, and User Satisfaction. A total of 315 respondents who have used the Jambi District Court’s website participated in this study. The data was processed using SPSS 2.5 software. The results show that only one variable, Service Interaction, has a significant effect on satisfaction, while the other two variables, Usability Quality and Information Quality, do not have a significant impact on satisfaction.